Urbanisation-induced changes in the morphology of birds from a tropical city - Santos, Eduardo Guimarães; Pompermaier, Vinicius Tirelli; Wiederhecker, Helga Correa; Marini, Miguel Ângelo (Emu, 2023)
Urbanisation is accompanied by major environmental changes that impact the structure and functioning of communities and ecosystems, bringing new selective regimes for animal species and for eco-evolutionary dynamics. We aimed to evaluate whether urban intensification promotes ecomorphological changes in birds from a large city in Central Brazil. Analyses were performed on a set of 1314 individuals of 35 species, captured along a gradient of urban intensification. We found significant morphological changes associated with urban intensification by evaluating ten ecomorphological traits and body mass of the species assemblage. Beak length showed the most dramatic changes, and was significantly shorter as a function of urban intensification, mainly in individuals of insectivorous and omnivorous species. These results reinforce the notion that environmental changes caused by human activities in dense urban environments promote new selective pressures in resident bird species.